"Crafting" masculinity: negotiating masculine identities in the Japanese workplace - Dasgupta, Romit (Curtin University, 2004)
Underlying the process by which Japan emerged as a global industrial power in the twentieth century was a particularly powerful ideology of gender and sexuality which equated masculinity with the public/work sphere and femininity with the private household sphere. Within this ideological framework, the archetypal male citizen - indeed, the ‘ideal’ male citizen - over the post-World War Two decades came to be represented by the ‘salaryman’ (sarariirnan, in Japanese). The term referred to permanent, predominantly white-collar, male private-sector employees, who were seen as being the foot-soldiers, the kigyô senshi (‘corporate warriors’) of Japan’s high-speed economic growth over the 1960s, 1970s. and even into the 1980s. Even after the slowing down of economic growth from the 1990s. the salaryman, and all that the discourse of masculinity built up around him represented, has continued to exert a powerful presence on the social landscape. This is despite the fact that, even at the high-point of economic growth in the 1960s and 1970s, only a minority of men would have fallen within the strictest definitional parameters of the term. However, it was the discourse associated with the salaryman - one infused with the gender ideology of the male breadwinner - that was far more extensive in its reach. In this respect the form of masculinity associated with the salaryman may be regarded as what R.W. Connell terms ‘hegemonic masculinity’.This thesis explores the ways in which the discourse of salaryman masculinity became the hegemonic form of masculinity in Japan over the postwar decades, and the ways in which it continues to operate in present-day Japan. In exploring the dynamics at work, the thesis draws attention to the fact that rather than being some kind of immutable, biologically determined ‘given’, masculinity is a constantly shifting process. Indeed, rather than a single overarching masculinity, there are multiple masculinities at work. It is within the context of this matrix of masculinities that one particular form - the hegemonic masculinity - has the greatest ideological power. However hegemonic masculinity itself has to be constantly ‘crafted’ and ‘re-crafted’ through engagements with other masculinities. This occurs both at the wider societal level, and at the level of the individual. Consequently the discussion in this thesis is carried out at both the ‘macro’ societal level, and at the ‘micro’ level of the individual. The former level of analysis situates the emergence of the discourse of salaryman masculinity within the historical framework of Japan’s modernization and nation-building project, and also examines the ways in which socio-cultural spaces such as popular culture were, and continue to be, significant in the process. The second level of analysis explores the dynamics of the ‘crafting’ of hegemonic masculinity at the level of the individual male. The discussion draws upon intensive interviews carried out with young male employees of two private sector civilization, during an eighteen-month period of fieldwork.It explores the ways in which these informants negotiate with the ideological expectations of salaryman masculinity vis-a-vis their own masculine identities, expectations which encompass various aspects of their lives. The discussion at both the ‘macro’ and micro’ level of analysis reveals that the dynamics of ‘crafting’ masculinity, rather than being a tidy, easy-to-categorize process, are infused with ambiguity, contradictions, richness, and nuance. It is through these contradictions that the contours of hegemonic masculinity are shaped and re-shaped.